2019
DOI: 10.1002/ptr.6348
|View full text |Cite
|
Sign up to set email alerts
|

Ficus extract—A promising agent for antimammary tumorigenesis: A review on current status and future possibilities

Abstract: Pharmacological studies have shown that various species of Ficus have antiviral, antidiarrheal, antipyretic, hypolipidemic, antidiabetic, antioxidant, anticancer, antiparasitic, antiangiogenic, anti‐inflammatory, antibacterial, antiplatelet, reproductive, dermatological, immunological, endocrine, and hepato and nephron protective effects. But there is no sufficient research on biomolecules present in the leaf extract of Ficus religiosa and its mechanism of action. We have previously reported that bioavailable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…For example, cisplatin mediates apoptosis by increasing ROS production in malignant human testicular germ cells 54 . Remadevi et al reported that Ficus extract induce apoptosis through the generation of intracellular ROS on breast cancer cells 38 . Our results demonstrated that the FSB increase ROS production in an dose‐dependent manner in SCC2095 cells.…”
Section: Discussionsupporting
confidence: 57%
“…For example, cisplatin mediates apoptosis by increasing ROS production in malignant human testicular germ cells 54 . Remadevi et al reported that Ficus extract induce apoptosis through the generation of intracellular ROS on breast cancer cells 38 . Our results demonstrated that the FSB increase ROS production in an dose‐dependent manner in SCC2095 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Multiple studies describe the anticancer potential of Ficus spp, ex. Ficus carica [ 46 , 47 ], Ficus salicifolia [ 46 ], Ficus religiosa [ 48 ], Ficus beecheyana [ 49 ], Ficus pandurata H [ 50 ] and Ficus exasperata (Vahl) [ 51 ], against various cancer cell lines, however, to the best of our knowledge, this is the first report showing Ficus sur stem bark extracts as a possible source of antineoplastic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several studies report the ability of these plant extracts to inhibit the proliferation mainly of breast cancer cells, but also of hematological cancer [47,48]. 14, caffeic acid (15), trigonelline (16), formic acid (17). Spectra were measured in D2O-buffer (pH 6.0) using TMSP as standard, residual water signal has been removed.…”
Section: Phytochemical Analysesmentioning
confidence: 99%
“…Spectra were measured in D2O-buffer (pH 6.0) using TMSP as standard, residual water signal has been removed. (14), caffeic acid (15), trigonelline (16), formic acid (17). Spectra were measured in D 2 O-buffer (pH 6.0) using TMSP as standard, residual water signal has been removed.…”
Section: Phytochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation